Nanomaterial-mediated autophagy: coexisting hazard and health benefits in biomedicine - Xiaoli Feng; Yaqing Zhang; Chao Zhang; Xuan Lai; Yanli Zhang; Junrong Wu; Chen Hu; Longquan Shao (Particle and Fibre Toxicology, 2020)
Abstract Background Widespread biomedical applications of nanomaterials (NMs) bring about increased human exposure risk due to their unique physicochemical properties. Autophagy, which is of great importance for regulating the physiological or pathological activities of the body, has been reported to play a key role in NM-driven biological effects both in vivo and in vitro. The coexisting hazard and health benefits of NM-mediated autophagy in biomedicine are nonnegligible and require our particular concerns. Main body We collected research on the toxic effects related to NM-mediated autophagy both in vivo and in vitro. Generally, NMs can be delivered into animal models through different administration routes, or internalized by cells through different uptake pathways, exerting varying degrees of damage in tissues, organs, cells, and organelles, eventually being deposited in or excreted from the body. In addition, other biological effects of NMs, such as oxidative stress, inflammation, necroptosis, pyroptosis, and ferroptosis, have been associated with autophagy and cooperate to regulate body activities. We therefore highlight that NM-mediated autophagy serves as a double-edged sword, which could be utilized in the treatment of certain diseases related to autophagy dysfunction, such as cancer, neurodegenerative disease, and cardiovascular disease. Challenges and suggestions for further investigations of NM-mediated autophagy are proposed with the purpose to improve their biosafety evaluation and facilitate their wide application. Databases such as PubMed and Web of Science were utilized to search for relevant literature, which included all published, Epub ahead of print, in-process, and non-indexed citations. Conclusion In this review, we focus on the dual effect of NM-mediated autophagy in the biomedical field. It has become a trend to use the benefits of NM-mediated autophagy to treat clinical diseases such as cancer and neurodegenerative diseases. Understanding the regulatory mechanism of NM-mediated autophagy in biomedicine is also helpful for reducing the toxic effects of NMs as much as possible.